Long-Term Outcome After Catheter Ablation of Ventricular Tachycardia in Patients With Nonischemic Dilated Cardiomyopathy. (October 2016) - Muser, Daniele; Santangeli, Pasquale; Castro, Simon A.; Pathak, Rajeev K.; Liang, Jackson J.; Hayashi, Tatsuya; Magnani, Silvia; Garcia, Fermin C.; Hutchinson, Mathew D.; Supple, Gregory G.; Frankel, David S.; Riley, Michael P.; et al.
Abstract : Background—: Catheter ablation (CA) of ventricular tachycardia (VT) in patients with nonischemic dilated cardiomyopathy can be challenging because of the complexity of underlying substrates. We sought to determine the long-term outcomes of endocardial and adjuvant epicardial CA in nonischemic dilated cardiomyopathy. Methods and Results—: We examined 282 consecutive patients (aged 59±15 years, 80% males) with nonischemic dilated cardiomyopathy who underwent CA. Ablation was guided by activation/entrainment mapping for tolerated VT and pacemapping/targeting of abnormal electrograms for unmappable VT. Adjuvant epicardial ablation was performed for recurrent VT or persistent inducibility after endocardial–only ablation. Epicardial ablation was performed in 90 (32%) patients. Before ablation, patients failed a median of 2 antiarrhythmic drugs), including amiodarone, in 166 (59%) patients. The median follow-up after the last procedure was 48 (19–67) months. Overall, VT-free survival was 69% at 60-month follow-up. Transplant-free survival was 76% and 68% at 60- and 120-month follow-up, respectively. Among the 58 (21%) patients with VT recurrence, CA still resulted in a significant reduction of VT burden, with 31 (53%) patients having only isolated (1–3) VT episodes in 12 (4–35) months after the procedure. At the last follow-up, 128 (45%) patients were only on β-blockers or no treatment, 41 (15%) were on sotalol or class I antiarrhythmic drugs, and 62 (22%) were on amiodarone. Conclusions—: In patients with nonischemic dilated cardiomyopathy and VT, endocardial and adjuvant epicardial CA is effective in achieving long-term VT freedom in 69% of cases, with a substantial improvement in VT burden in many of the remaining patients. Abstract : Supplemental Digital Content is available in the text.